PLOUGHING OF WORK-HARDENING ASPERITIES BY A HEMISPHERICAL SLIDER (Journal of Engineering, 2008)
A theoretical description is given for the ploughing of a work-hardening inclined surface by a hemispherical slider. As the indenture is moving horizontally, the grooving force and the depth of penetration are expressed for conditions that correspond to the climbing and descending asperities. Assuming a constant vertical load on the slider, the friction coefficient due to ploughing, FP, is shown to be affected by surface inclination moreover, the limiting value of FP when the vertical load on slider is made infinitely small is shown to be independent upon the asperity angle and the shape of the slider. The treatment has some use in predicting the extent of surface damage in contact profilometry, especially for soft materials in particular, the depth of penetration is shown to be different when climbing or descending a surface whose inclination is  .